THE INFLUENCE OF THE INTERNAL CONTROL SYSTEM AND INDIVIDUAL MORALITY ON FRAUD IN VILLAGE FUND MANAGEMENT - Sarmigi, Elex; Surya, Tiara Lilis; Maryanto, Maryanto; Salsabela, Ica (Jurnal Al-Iqtishad, 2023)
This study aims to determine the effect of the internal control system and individual morality on the tendency to fraud in managing village funds in the Kumun Debai sub-district, Sungai Full City. The sample of this study was all employees of the village government head office of Kumun Debai Sub-District, Sungai Full City, totalling 72 people, who were determined by the full sampling method. Testing the research data was analyzed with multiple linear regression. This study found that the internal control system had a negative and significant effect on the tendency to fraud in managing village funds. Meanwhile, individual morality has no significant effect on the tendency of fraud in managing village funds. The magnitude of the influence of the internal control system and individual morality on the tendency of fraud in managing village funds is 40.5%.